Role of Extracorporeal Membrane Oxygenation in Adults and Children With Refractory Septic Shock: A Systematic Review and Meta-Analysis - Yang, Yufan; Xiao, Zhenghui; Huang, Jiaotian; Gong, Ling; Lu, Xiulan (Frontiers in Pediatrics, 2022)
Background: The benefits of extracorporeal membrane oxygenation (ECMO) in patients with refractory septic shock remain controversial. Current guidelines on the management of refractory septic shock recommend the consideration of ECMO as a salvage therapy. The difference between adults and children with septic refractory shock treated with ECMO has not been previously analyzed. We aimed to review peer-reviewed publications on the role of ECMO in adults and children with refractory septic shock. Methods: Studies reporting on mortality in both adults and children with refractory septic shock supported with ECMO published in PubMed, Cochrane Library, and Embase databases were included in the meta-analysis. Study eligibility was independently assessed by two authors, and disagreements were resolved by a third author. The outcome measure was survival at discharge. Subgroup analysis included the adult and pediatric groups. Results: Of the 293 articles screened, 13 original articles were identified for systematic review and meta-analysis. The cumulative estimate of survival (13 studies, 465 patients) in the cohort was 38% (95% confidence interval [CI]: 26%–51%). During the subgroup analysis, the cumulative estimate of survival at discharge in the adult group (6 studies, 276 patients) in the cohort was 18% (95% CI: 10%–27%), and that in the pediatric group (7 studies, 189 patients) was 56% (95% CI: 49%–63%). Conclusions: The survival rate of adults with refractory septic shock requiring ECMO was 18%, and children with refractory septic shock requiring ECMO had a higher survival rate (56%) than adults. Keywords: Children, refractory septic shock, extracorporeal membrane oxygenation, adults.